2023
DOI: 10.1021/acs.joc.2c02756
|View full text |Cite
|
Sign up to set email alerts
|

Selectfluor-Mediated Regioselective C-3 Alkoxylation, Amination, Sulfenylation, and Selenylation of Quinoxalin-2(1H)-ones

Abstract: A Selectfluor-promoted oxidative coupling of quinoxalin-2(1H)-ones with alcohols, amines, thiols, and selenols leading to the formation of C–O, C–N, C–S, and C–Se bonds has been developed. The protocol provided good to excellent (53–95%) yields of a wide range of quinoxalin-2(1H)-ones decorated with alkoxy, alkylamino, alkylthio, and arylselenyl groups at the C3-position under metal- and photocatalyst-free conditions. The reaction is believed to proceed through a radical pathway. A broad substrate scope includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The crude material was purified by flash column chromatography (silica gel, petroleum ether/EtOAc = 5:1) to give 3j as a white solid (32.6 mg, 67% yield); 1 H NMR (400 MHz, CDCl 3 ) δ 7.56 (q, J = 7.2 Hz, 1H), 7.23 (td, J = 6.0, 2.4 Hz, 1H), 7.17 (dd, J = 5.1, 2.2 Hz, 2H), 6.40 (s, 1H), 5.94 (ddt, J = 17.2, 10.3, 5.0 Hz, 1H), 5.25 (dd, J = 10.4, 0.8 Hz, 1H), 5.17 (dd, J = 17.2, 0.7 Hz, 1H), 4.90 (dt, J = 4.9, 1.7 Hz, 2H), 3.51 (q, J = 7.2 Hz, 2H), 1.77–1.67 (m, 2H), 1.03 (t, J = 7.4 Hz, 3H) ppm; 13 C { 1 H} NMR (100 MHz, CDCl 3 ) δ 151.6, 148.9, 134.4, 130.8, 128.4, 126.2, 124.1, 123.7, 117.8, 114.1, 44.7, 42.6, 22.4, 11.6 ppm; the spectral data obtained were identical with those reported in the literature …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crude material was purified by flash column chromatography (silica gel, petroleum ether/EtOAc = 5:1) to give 3j as a white solid (32.6 mg, 67% yield); 1 H NMR (400 MHz, CDCl 3 ) δ 7.56 (q, J = 7.2 Hz, 1H), 7.23 (td, J = 6.0, 2.4 Hz, 1H), 7.17 (dd, J = 5.1, 2.2 Hz, 2H), 6.40 (s, 1H), 5.94 (ddt, J = 17.2, 10.3, 5.0 Hz, 1H), 5.25 (dd, J = 10.4, 0.8 Hz, 1H), 5.17 (dd, J = 17.2, 0.7 Hz, 1H), 4.90 (dt, J = 4.9, 1.7 Hz, 2H), 3.51 (q, J = 7.2 Hz, 2H), 1.77–1.67 (m, 2H), 1.03 (t, J = 7.4 Hz, 3H) ppm; 13 C { 1 H} NMR (100 MHz, CDCl 3 ) δ 151.6, 148.9, 134.4, 130.8, 128.4, 126.2, 124.1, 123.7, 117.8, 114.1, 44.7, 42.6, 22.4, 11.6 ppm; the spectral data obtained were identical with those reported in the literature …”
Section: Methodsmentioning
confidence: 99%
“…The crude material was purified by flash column chromatography (silica gel, petroleum ether/EtOAc = 5:1) to give 3a as a white solid (41.7 mg, 96% yield); 1 H NMR (400 MHz, CDCl 3 ) δ 7.55 (dd, J = 6.8, 2.3 Hz, 1H), 7.26–7.21 (m, 3H), 6.39 (s, 1H), 3.71 (s, 3H), 3.51 (q, J = 7.2 Hz, 2H), 1.76–1.67 (m, 2H), 1.02 (t, J = 7.4 Hz, 3H) ppm; 13 C { 1 H} NMR (100 MHz, CDCl 3 ) δ 152.0, 149.0, 134.3, 129.4, 126.1, 124.2, 123.8, 113.6, 42.6, 29.4, 22.5, 11.6 ppm; the spectral data obtained were identical with those reported in the literature …”
Section: Methodsmentioning
confidence: 99%
“…Quinoxalin-2(1 H )-ones have a wide range of applications in materials science as well ( Scheme 2 ) [ 22 , 23 ]. The direct C–H functionalisation of quinoxalin-2(1 H )-one at the C3 position is the most cost-effective method for the synthesis of quinoxalin-2(1 H )-one derivatives, and a large number of studies have appeared in this field in recent years [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. A Web of Science search revealed that the number of papers related to quinoxalin-2(1 H )-one has increased year by year over the last five years, with a total of 25 in 2018, 57 in 2019, 61 in 2020, 92 in 2021, and 95 in 2022.…”
Section: Introductionmentioning
confidence: 99%